2018
DOI: 10.1002/nbm.4005
|View full text |Cite
|
Sign up to set email alerts
|

CEST‐MRI for glioma pH quantification in mouse model: Validation by immunohistochemistry

Abstract: In glioma, the acidification of the extracellular tumor microenvironment drives proliferation, angiogenesis, immunosuppression, invasion and chemoresistance. Therefore, quantification of glioma extracellular pH (pHe) is of crucial importance. This study is focused on the application of the YbHPDO3A (ytterbium 1,4,7-triscarboxymethyl-1,4,7,10-tetraazacyclododecane) probe for in vivo glioma pHe quantification using chemical exchange saturation transfer (CEST)-MRI and its correlation with tumor metabolism assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 56 publications
(177 reference statements)
0
25
0
Order By: Relevance
“…Alternative endogenous CEST MRI methods such as AACID (34) have been used in this way to investigate the tumour pH change associated with administration of dichloroacetate (35), topiramate (36) and lonidamine (37) in preclinical experiments. Additionally, exogenous diaCEST (3841) and paraCEST (42,43) contrast agents have been developed that successfully measure tumour extracellular pH, though these methods are limited by contrast agent availability to the tumour, which may be limited in areas of particularly poor perfusion (44) or in the brain where the blood-brain barrier may be partially intact in the early stages of tumour growth.…”
Section: Discussionmentioning
confidence: 99%
“…Alternative endogenous CEST MRI methods such as AACID (34) have been used in this way to investigate the tumour pH change associated with administration of dichloroacetate (35), topiramate (36) and lonidamine (37) in preclinical experiments. Additionally, exogenous diaCEST (3841) and paraCEST (42,43) contrast agents have been developed that successfully measure tumour extracellular pH, though these methods are limited by contrast agent availability to the tumour, which may be limited in areas of particularly poor perfusion (44) or in the brain where the blood-brain barrier may be partially intact in the early stages of tumour growth.…”
Section: Discussionmentioning
confidence: 99%
“…Cross-linked albumin was obtained by using a well-established procedure 27,28 . Briefly, BSA (Bovine Serum Albumin, Sigma Aldrich) was dissolved in water (150 mg/mL) and the solution placed in a heated bath at 80 °C for 10 minutes.…”
Section: Methodsmentioning
confidence: 99%
“…Yb 3+ -HPDO3A showed a pH sensitivity in the range 6.5-8.0 at a field strength of 7 T and demonstrated in vivo tumor pHe maps in a murine melanoma model [96]. In a recent study using Yb 3+ -HPDO3A, it was shown that tumor pHe mapping can also provide information about tumor aggressiveness in a rat glioma model [97]. The advantage of PARACEST agents endowed with highly shifted resonances is further witnessed in the case of Tm 3+ -HPDO3A pH-sensitive agent, which allows in vivo tumor pH mapping at lower magnetic fields (1 T), due to the far-shifted hydroxyl resonances of the two diastereoisomers (71 and 185 ppm, respectively) [98].…”
Section: Paramagnetic Ph-responsive Probes (Paracest)mentioning
confidence: 99%